Crime Families in the Maltese Islands: A Spatial Perspective - Formosa Pace, Janice (Advances in Social Sciences Research Journal, 2025)
This study explores the potential role of spatial factors as crime promoters to intergenerational continuity of offending in the Maltese Islands. The intergenerational dataset created for the Formosa Pace 2014 study, covering incarcerations between 1950 and 2010 is used to explore such phenomena. The focus here is on the residential location of individuals belonging to the intergenerational cohort using street level analysis to explore potential risks linked to spatial proximity. A spatial analysis is employed to examine the crime families’ residential zones vis-a-vis the offender and poverty hotspots identified in the Formosa 2007 study. This explores further the relationship between the location of crime families and the socio-demographic factors in communities that could serve as “activity fields” for crime continuity. Crime runs and concentrates in a relatively small number of Maltese families across 2 to 5 generations, wherein family members act as crime role models. Crime continuity is accommodated by a number of crime promoters that present themselves in the activity field. These include geographical proximity, residing in intersecting poverty and offender hotspots as well as exposure to crime role models within the family and the community. Thus, a series of crime promoters act as direct or indirect transmission risks to crime continuity wherein communities such as Valletta, Bormla and Santa Lucija allow for transgenerational transmission.